(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
In the context of communication and management, thoughts, data, perceptions and feelings regarding job success, operational productivity and efficiency as well as objectives attainment are created, communicated and interpreted in an organization. A management must be a good communicator because no company can prosper or advance without strong communications skills. A study which discus about Communication, Communication Represents You and Your Employer, Importance of communication, Technology and Business Communication, The Need for Good Communication in Organizations, Managing Communication in Organizations, Types of Business Communication, Elements of Business Communication, Features of Business Communication.